Bilateral primary eyelid meibomian gland epithelioma in a dog: a case report - KOMNENOU, A.; CHARALAMBIDOU, G.; MAKROGKIKAS, S.; PAPAIOANNOU, N. (Journal of the Hellenic Veterinary Medical Society, 2019)
In this paper an extremely rare case of primary bilateral eyelid meibomian gland epithelioma in a dog is presented. Meibomian tumors arise from the meibomian (tarsal) glands on the inner aspect of the eyelid, and meibomian gland adenomas and adenocarcinomas are the most frequent neoplasia arising from those glands. A 10-year-old male dog was admitted, with ophthalmic signs of periorbital swelling of the right eye. During the last two years, the dog had a progressive engorgement of the upper eyelid of the right eye, and during the past few months, strabismus and exophthalmos were also noticed, as well as a slighter enlargement on the lower eyelid of the left eye. Upon ophthalmic examination strabismus and periorbital swelling at the lateral canthus of the right eye, accompanied by mild exophthalmos and lagophthalmos, were recorded. Also, deep ulcerative keratitis with corneal oedema and neovascularization were noticed. Intense chemosis, epiphora and a small pinkish mass arising from the palpebral conjunctiva of the left lower eyelid were also seen. Neoplasia of both eyelids was suspected, and a series of diagnostic examinations were carried out. Orbital exenteration of the right eye was performed in the first place, followed by surgical removal of the mass of the left eyelid one month later. Based on clinical and histopathological findings, meibomian gland epithelioma was diagnosed. No relapse or metastases (local or distant) were observed in re-examinations within 18 months after the surgery. This study shows that although meibomian gland epithelioma is rare, it should be considered in the differential diagnosis of cases of orbital and eyelid tumors. Even though this tumor shows low malignancy, prompt surgical intervention and extended excision is the treatment of choice, in order to preserve vision in some cases. To the authors’ knowledge, the present case is the first report of bilateral meibomian gland epithelioma in the veterinary literature.